2018
DOI: 10.13168/agg.2018.0030
|View full text |Cite
|
Sign up to set email alerts
|

Creep behavior and acoustic emission characteristics of coal samples with different moisture content

Abstract: The acoustic emission (AE) test of step-loaded samples of coal with different moisture contents was conducted using an AG-X250KN rock servo test system and an AE21C AE-monitoring system to study the influence of moisture content on the creep characteristics of coal. The results show that the moisture content influences the creep characteristics of coal samples, in that the greater the moisture content, the greater the creep deformation of the coal and the lower the creep threshold, creep strength, and creep co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Acoustic emission (AE) activities of rock are mainly caused by the generation, expansion, and fracture of cracks inside the rock and can reveal the damage of the rock [33]. e acoustic emission information of compressed rock contains abundant precursor information of rock failure, which is of great significance for predicting the damage process of rock [34].…”
Section: Analysis Of Acoustic Emission Characteristicsmentioning
confidence: 99%
“…Acoustic emission (AE) activities of rock are mainly caused by the generation, expansion, and fracture of cracks inside the rock and can reveal the damage of the rock [33]. e acoustic emission information of compressed rock contains abundant precursor information of rock failure, which is of great significance for predicting the damage process of rock [34].…”
Section: Analysis Of Acoustic Emission Characteristicsmentioning
confidence: 99%
“…In 1939, Griggs performed creep studies on rock and reported that rock deformation varied with time at a certain stress level (Griggs, 1939). Researchers have made great efforts to perform experiments to analyze features on different kinds of rock, such as granite (Lin et al, 2009;Chen et al, 2015;Xu et al, 2017), shale (Sone and Zoback, 2014), rock salt (Mansouri and Ajalloeian, 2018), sandstone (Brantut et al, 2014b;Chen et al, 2018), limestone (Brantut et al, 2014a;Nicolas et al, 2017), and coal (Ma et al, 2018;Zhang et al, 2019). Additionally, effects of loading history, including single-stage, multi-level loading (Zhao et al, 2017b;Yang et al, 2018), cycle loading and unloading (Chen et al, 2018) were investigated, and numerous researches focused on the temperatures (Xu et al, 2017), water (Liu and Shao, 2017;Yu C. et al, 2019), as well as initial porosity (Brantut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…AE is directly related to the microfractures in rocks and can be expressed by the damage parameters of rocks. Because the AE signals contain abundant information about crack changes, a number of studies have used AE to investigate the evolution law of crack and rock fracture patterns in Brazilian splitting tests, three-point bending, and compression [11][12][13][14][15][16][17][18][19]. It is found that there are inevitably subjectivity and uncertainty in the process of determining rock deformation by using the crack volume strain method [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%